Proceedings of the 5th International Workshop on Emerging Trends in Software Metrics 2014
DOI: 10.1145/2593868.2593880
|View full text |Cite
|
Sign up to set email alerts
|

A security metric based on security arguments

Abstract: Software security metrics that facilitate decision making at the enterprise design and operations levels are a topic of active research and debate. These metrics are desirable to support deployment decisions, upgrade decisions, and so on; however, no single metric or set of metrics is known to provide universally effective and appropriate measurements. Instead, engineers must choose, for each software system, what to measure, how and how much to measure, and must be able to justify the rationale for how these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…The model that suggests itself in this context is not measurement of an observable property, but rather a quantification of defensible belief using Bayesian, Dempster-Shafer [102], or other similar theories. The relationship between this kind of metric and an assurance case, which also focuses on evidential reasoning, was described in [103].…”
Section: Securitymentioning
confidence: 99%
“…The model that suggests itself in this context is not measurement of an observable property, but rather a quantification of defensible belief using Bayesian, Dempster-Shafer [102], or other similar theories. The relationship between this kind of metric and an assurance case, which also focuses on evidential reasoning, was described in [103].…”
Section: Securitymentioning
confidence: 99%
“…We also looked into the authors of the selected papers to find the portion of the papers with at least one author from industry. We found that less than 25% (12 papers) (Cockram and Lautieri 2007;Goodger et al 2012;Netkachova et al 2015;Netkachova and Bloomfield 2016;Xu et al 2017;Gacek et al 2014;Rodes et al 2014;Bloomfield et al 2017;Netkachova et al 2014;Gallo and Dahab 2015;Cheah et al 2018;Ionita et al 2017) included at least one author from industry.…”
Section: Descriptive Statisticsmentioning
confidence: 82%
“…We also looked into the authors of the selected papers to find the portion of the papers with at least one author from industry. We found that less than 25% (12 papers) [16,28,51,50,79,24,57,11,49,26,14,38] included at least one author from industry.…”
Section: Descriptive Statisticsmentioning
confidence: 89%
See 2 more Smart Citations